(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
This paper gives a brief description of the development of general methods of integrating ordinary differential equations from its beginning in 1675 until 1775 when the search for such methods ended. The focus of the paper is the historical roots of nine mathematical problems that led to the independent discipline now called Ordinary Differential Equations.